2011
DOI: 10.1002/pip.1168
|View full text |Cite
|
Sign up to set email alerts
|

Improved micromorph solar cells by means of mixed‐phase n‐doped silicon oxide layers

Abstract: A good light trapping scheme is necessary to improve the performance of amorphous/microcrystalline silicon tandem cells. This is generally achieved by using a highly reflective transparent conducting oxide/metal back contact plus an intermediate reflector between the component cells. In this work, the use of doped silicon oxide as alternative n‐layer in micromorph solar cells is proposed as a means to obtain high current values using a simple Ag back contact and no extra reflector between the component cells n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Function n p-μc-SiOx:H p-type layer 2.97-3.5 [5,13] n-μc-SiOx:H n-type layer + IRL 1.8-2.6 [9,10,14,15] SiOx IRL 2.0 [12,16] Table 1 gives a summary of n values reported in the literature for such films. The electrical conductivity of doped μc-SiO x :H is attributed to the presence of doped microcrystalline silicon filaments in an amorphous silicon oxide matrix, which results in an out-of-plane conductivity of the layers above 10 −5 S/cm, while their in-plane conductivities are below 10 −10 S/cm [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Function n p-μc-SiOx:H p-type layer 2.97-3.5 [5,13] n-μc-SiOx:H n-type layer + IRL 1.8-2.6 [9,10,14,15] SiOx IRL 2.0 [12,16] Table 1 gives a summary of n values reported in the literature for such films. The electrical conductivity of doped μc-SiO x :H is attributed to the presence of doped microcrystalline silicon filaments in an amorphous silicon oxide matrix, which results in an out-of-plane conductivity of the layers above 10 −5 S/cm, while their in-plane conductivities are below 10 −10 S/cm [9].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, doped microcrystalline silicon oxide (μc-SiO x :H) is a material which has gained scientific interest because of it having a reduced optical absorption and low refractive index, while still generating sufficient built-in potential across the absorber layer for electron-hole separation [5][6][7][8]. It has been demonstrated that it is possible to control the refractive index (n) of undoped and doped μc-SiO x :H in the range from 1.8-3.6 [9][10][11] and that these layers can be designed for several functions in thin film silicon solar cells, namely as a doped layer or as an intermediate reflector layer (IRL) [12]. a e-mail: prabal.goyal@polytechnique.edu Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…-Improve the light management [9][10][11][12][13][14]: transparent intermediate reflector layer in micromorph solar cells and reduced parasitic absorption (for instance highly transparent window layer). -Increase electrical performance and cell resilience to the substrate texture [1,[5][6]: electrical performance gain scales with substrate roughness, and up to 6 % and 20 % gains were demonstrated respectively for a-Si:H and μc-Si:H p-i-n junctions [1].…”
Section: Cell Architecture and Pecvd Process Conditions For Textumentioning
confidence: 99%
“…• the CO 2 concentration • the doping concentration • the layer thickness We decided to use an amorphous n-layer instead of the commonly used μc-Si 1-X O X :H layer [9,10] because we expected a better long-term stability of highly doped amorphous n-layers compared to highly doped μc-Si 1-X O X :H layers [work in prep.]. Furthermore, the process stability is better.…”
Section: Methodsmentioning
confidence: 99%